2009
DOI: 10.1002/cvde.200906810
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Niobium Nitride Thin Films from Tert‐Butylamido‐Tris‐(Diethylamido)‐Niobium by a Modified Industrial MOCVD Reactor

Abstract: Niobium nitride thin films are deposited on 2 00 silicon (100) wafers using a modified industrial metal-organic (MO) CVD reactor of the type AIX-200RF, starting from tert-butylamido-tris-(diethylamido)-niobium (TBTDEN) and ammonia. Films of thicknesses 50-200 nm are deposited at temperatures ranging from 400 8C to 800 8C under reactor pressures of 1 and 5 mbar using various ammonia flow rates, and are characterized by the use of complementary techniques, namely X-ray diffraction (XRD), scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Similarly, the O 1s core level spectrum (Figure S4b, Supporting Information) could also be fitted with two peaks located at around 530.7 and 532.3 eV. The former is characteristic of oxygen in Nb 2 O 5 , while the latter is associated with oxygen in NbNO, and even in some CO and OH bonds.…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, the O 1s core level spectrum (Figure S4b, Supporting Information) could also be fitted with two peaks located at around 530.7 and 532.3 eV. The former is characteristic of oxygen in Nb 2 O 5 , while the latter is associated with oxygen in NbNO, and even in some CO and OH bonds.…”
Section: Resultsmentioning
confidence: 76%
“…14 It was shown that amido and imido ligands are useful for the synthesis of transition-metal complexes, which can act as precursors for transition-metal nitrides. [15][16][17][18][19][20][21][22] More recently, all-nitrogen-coordinated, heteroleptic derivatives of the simple amido/imido-compounds containing chelating monoanionic guanidinato ligands, {(R 0 N) 2 C(NR 00 2 )} -(R 0 , R 00 = alkyl substituents, such as Me, Et, i Pr), in the coordination sphere of Ta, Nb, Mo, and W were investigated, and, in some cases, superior performance as precursors for the nitrides was reported. 23,24 We successfully transferred these precursor concepts to the family of homoleptic guanidinato precursors of lanthanide metals with GdN as a representative test case.…”
Section: ' Introductionmentioning
confidence: 99%
“…This is especially true for metal nitride precursors . It was shown that amido and imido ligands are useful for the synthesis of transition-metal complexes, which can act as precursors for transition-metal nitrides. More recently, all-nitrogen-coordinated, heteroleptic derivatives of the simple amido/imido-compounds containing chelating monoanionic guanidinato ligands, {(R′N) 2 C(NR′′ 2 )} − (R′, R′′ = alkyl substituents, such as Me, Et, i Pr), in the coordination sphere of Ta, Nb, Mo, and W were investigated, and, in some cases, superior performance as precursors for the nitrides was reported. , We successfully transferred these precursor concepts to the family of homoleptic guanidinato precursors of lanthanide metals with GdN as a representative test case. [Gd{( i PrN) 2 C(NMe 2 )} 3 ] ( 1 ) turned out to be a surprisingly good single-source precursor for the growth of phase-pure, rock salt GdN by MOCVD, and similar behavior was indicated for the dysprosium analogue [Dy{( i PrN) 2 C(NMe 2 )} 3 ] ( 2 ). , Employing high-resolution electron impact mass spectrometry (HR EI-MS), the Gd-imido species were detected in the course of the fragmentation of 1 , supporting the idea that the guanidinato ligand serves as a source for the N component under single-source MOCVD conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…Due to the high volatility of the Mo framework ameliorated by the DAD ligand, herein we explore the use of the same framework for other refractory metals. Alkylimide ligands have been used repeatedly to deposit vanadium, niobium, tantalum, ,, molybdenum, , and tungsten nitride films by CVD (Chart ), , demonstrating that the compounds presented herein could afford viable refractory metal CVD precursors due to the tert -butylimide moieties of the bis­( tert -butylimide)­dichloride DAD framework.…”
Section: Introductionmentioning
confidence: 97%